Hematopoietic stem/progenitor cell differentiation towards myeloid lineage is modulated by LIGHT/LIGHT receptor signaling. Issue 2 (24th May 2017) - Chen, Weikai; Lv, Xin; Liu, Changlong; Chen, Ruoping; Liu, Jianhe; Dai, Haiyan; Zou, Gang‐Ming
Abstract : The cytokine LT‐related inducible ligand that competes for glycoprotein D binding to herpesvirus entry mediator on T cells (LIGHT) is a member of the tumor necrosis factor (TNF) superfamily. It is expressed primarily on activated T lymphocytes, and detectable on monocytes, granulocytes, and immune dendritic cells. It mainly plays a role in immune regulation including T cell activation and dendritic cell maturation. We recently reported its role as an inducer in embryonic stem cell differentiation, but its role in regulation of adult stem cell has not been defined. In the present study, we examined the expression of LIGHT receptor in Lin − c‐kit + Sca‐1 + hematopoietic stem/progenitor cells (HSC/HPCs). We found that HSC express HVEM, a LIGHT receptor, on its surface. We further identified the role of LIGHT in promoting myeloid differentiation of HSCs driven by granulocyte‐monocyte colony stimulating factor (GM‐CSF). Further studies showed that LIGHT enhances both GM‐CSF and GM‐CSF receptor (GM‐CSFR) expression in HSCs. LIGHT stimulation increases PU.1 expression in HSC/HPCs. In vivo administration of LIGHT increases the colony‐forming unit‐granulocyte/monocyte (CFU‐GM) colony formation and plasma GM‐CSF level. Altogether, the data suggest LIGHT promote myeloid differentiation of HSC/HPCs. Abstract : In the present study, we examined the expression of LIGHT receptor in Lin‐c‐kit+Sca‐1+ hematopoietic stem/progenitor cells (HSC/HPCs). We found that HSC express HVEM, a LIGHT receptor, on its surface. We further identified the role of LIGHT in promoting myeloid differentiation of HSCs driven by granulocyte‐monocyte colony stimulating factor (GM‐CSF).